The S1 Subunit of the SARS-CoV-2 Spike Protein Activates Human Monocytes to Produce Cytokines Linked to COVID-19: Relevance to Galectin-3 - Schroeder, John T.; Bieneman, Anja P. (Frontiers in Immunology, 2022)
Coronavirus disease 2019 (COVID-19), caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), rapidly evolved into a pandemic –the likes of which has not been experienced in 100 years. While novel vaccines show great efficacy, and therapeutics continue to be developed, the persistence of disease, with the concomitant threat of emergent variants, continues to impose massive health and socioeconomic issues worldwide. Studies show that in susceptible individuals, SARS-CoV-2 infection can rapidly progress toward lung injury and acute respiratory distress syndrome (ARDS), with evidence for an underlying dysregulated innate immune response or cytokine release syndrome (CRS). The mechanisms responsible for this CRS remain poorly understood, yet hyper-inflammatory features were also evident with predecessor viruses within the β-coronaviridae family, namely SARS-CoV-1 and the Middle East Respiratory Syndrome (MERS)-CoV. It is further known that the spike protein (S) of SARS-CoV-2 (as first reported for other β-coronaviruses) possesses a so-called galectin-fold within the N-terminal domain of the S1 subunit (S1-NTD). This fold (or pocket) shows structural homology nearly identical to that of human galectin-3 (Gal-3). In this respect, we have recently shown that Gal-3, when associated with epithelial cells or anchored to a solid phase matrix, facilitates the activation of innate immune cells, including basophils, DC, and monocytes. A synthesis of these findings prompted us to test whether segments of the SARS-CoV-2 spike protein might also activate innate immune cells in a manner similar to that observed in our Gal-3 studies. Indeed, by immobilizing S components onto microtiter wells, we show that only the S1 subunit (with the NTD) activates human monocytes to produce a near identical pattern of cytokines as those reported in COVID-19-related CRS. In contrast, both the S1-CTD/RBD, which binds ACE2, and the S2 subunit (stalk), failed to mediate the same effect. Overall, these findings provide evidence that the SARS-CoV-2 spike protein can activate monocytes for cytokines central to COVID-19, thus providing insight into the innate immune mechanisms underlying the CRS and the potential for therapeutic interventions.